Associations between interleukin 18 gene polymorphisms and susceptibility to vasculitis: A meta-analysis: IL18 polymorphisms in vasculitis - Jung, Jae Hyun; Jeong, Han Saem; Choi, Sung Jae; Song, Gwan Gyu; Kim, Jong-Ho; Lee, Tae Hyub; Han, Youngjin (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2020)
Interleukin 18 (IL18), a pro-inflammatory cytokine, affects the development and progress of vasculitis. The production, expression, and function of this cytokine are affected by polymorphisms of promoter region of the IL18 gene. In this study, a meta-analysis of the associations between several IL18 polymorphisms and susceptibility to vasculitis was performed. Published literature from PubMed and Embase were retrieved. In total, nine studies comprising 1006 patients with vasculitis and 1499 controls combined, and the investigating the rs187238, rs194618, and rs360719 polymorphisms of the promoter region of the IL18 gene, were included in the meta-analysis. Pooled odds ratios (OR) and 95% confidence intervals (CI) were estimated with fixed-effects model or random-effects model. The recessive model of the rs194618 polymorphism was found to be significantly associated with a high susceptibility to vasculitis (OR = 1.54, 95% CI = 1.02–2.33, P = 0.04), especially in the Mongoloid race, where the A allele of rs194618 was associated with a low risk of the disease (OR = 0.77, 95% CI = 0.62–0.95, P = 0.01). By contrast, the rs187238 and rs360719 polymorphisms were not associated with this inflammatory condition. This meta-analysis showed that some IL18 polymorphisms are associated with susceptibility to vasculitis.